Analysis of running motion in the starting phase of male skeleton athletes at international competitions - Oguchi, T.; Ae, M.; Schwameder, H.; Arii, S.; Harigai, R. (ISBS Proceedings Archive (Michigan), 2021)
The purpose of this research was to assess which kinematic factors were related to running speed in the starting phase for international-level skeleton athletes during races. The starting motion of 22 male athletes was recorded with four video cameras during competitions and their starting motion was analysed by a three-dimensional direct linear transformation method. The maximum angular velocity of the thigh increased from the 2nd to the 3rd step. The maximum hip extension angular velocity of the support leg gradually increased up until the 6th step while the maximum knee extension angular velocity remained constant throughout. It would appear that international-level male skeleton athletes employed an increase in thigh motion and quick hip and knee extension for the support leg to obtain a large running speed.